Polyporus spp. (POLYPORACEAE, BASIDIOMYCOTA): RARE RECORD FROM ECOSYSTEM OF FALLUJAH, IRAQ - Muslat, Mowafaq M.; Owaid, Mustafa N. (International Journal of Environment, 2015)
Based on morphological examination, genus of mushroom Polyporus sp. was identified, which constitutes the first record of this fungus in Iraq. It is necessary to study ecology of the rare species of polypores then conservation of their habitats. Because most of polypores live on the substrate of fallen trunks and rotten wood, it is very important to keep such substrate in the ecosystem. Polypors fungus was identified as genus level only which appeared on September 2013 in Fallujah city. The aim of this study to collect and identify of wild mushroom that grow naturally in different orchards and gardens. International Journal of Environment Volume-4, Issue-3, June-August 2015 Page: 185-189